Robotic-Assisted Laparoscopic Ovarian Cystectomy during Pregnancy - Carter, Susanna; Depasquale, Steven; Stallings, Shawn (American Journal of Perinatology Reports, 2011)
The use of robotic-assisted laparoscopic surgery (RALS) in gynecologic oncology is rising rapidly; however, the role of this modality in obstetrics has not been widely investigated. During pregnancy, the surgical management of adnexal masses is traditionally approached via laparotomy or laparoscopy. RALS offers a minimally invasive approach secondary to improved instrument dexterity and precision, 14-fold magnification, and 3-D imaging. For the pregnant patient, this translates into minimal manipulation of the gravid uterus, quicker recovery times, and potentially decreased maternal and fetal morbidity. Here we report six cases in which the da Vinci robotic surgical system (Intuitive Surgical Incorporated, Sunnyvale, CA) was used to perform an ovarian cystectomy during pregnancy. Pathology in all cases returned benign and each patient continued pregnancy without complications of surgery. In centers with the resources and adequately trained physicians, RALS offers the obstetric patient a safe and less invasive alternative to laparotomy or conventional laparoscopy. Although the advantages of robotic surgery are many, the limitations of this modality remain elevated equipment costs as well as the time investment necessary to train physicians.
Keywords: Robotic surgery; adnexal masses; complications of pregnancy